2022
DOI: 10.3390/jcm11133696
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Ciliary Body in Healthy Chinese Subjects Evaluated by Radial and Transverse Imaging of Ultrasound Biometric Microscopy

Abstract: Background: The imaging and analysis of the ciliary body (CB) are valuable in many potential clinical applications. This study aims to demonstrate the anatomy characteristics of CB using radial and transverse imaging of ultrasound biometric microscopy (UBM) in healthy Chinese subjects, and to explore the determining factors. Methods: Fifty-four eyes of 30 healthy Chinese subjects were evaluated. Clinical data, including age, body mass index (BMI), intraocular pressure (IOP), axial length (AL), and lens thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…12 The average CBTmax in our cohort (1.37 ± 0.11 mm) surpassed previously documented findings (1.25 ± 0.17 mm), possibly attributed to the predominantly young and highly myopic demographic in our study. 13,14 CPlength measures the length of ciliary process. 15 A longer ciliary process is usually accompanied by a thicker ciliary body and has been ascertained to be a risk factor for the excessive ICL vault.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The average CBTmax in our cohort (1.37 ± 0.11 mm) surpassed previously documented findings (1.25 ± 0.17 mm), possibly attributed to the predominantly young and highly myopic demographic in our study. 13,14 CPlength measures the length of ciliary process. 15 A longer ciliary process is usually accompanied by a thicker ciliary body and has been ascertained to be a risk factor for the excessive ICL vault.…”
Section: Discussionmentioning
confidence: 99%
“… 12 The average CBTmax in our cohort (1.37 ± 0.11 mm) surpassed previously documented findings (1.25 ± 0.17 mm), possibly attributed to the predominantly young and highly myopic demographic in our study. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…Of interest, a recent study conducted in healthy Chinese participants showed that the mean CPL was positively correlated with AL and negatively correlated with LT, which supported our findings of shorter AL and thicker LT in the insufficient vault group. 24 The space between the posterior surface of the iris and the anterior surface of the ciliary process has recently been proposed as a factor that may influence the vault. Wei et al used iris thickness to define the width of the ciliary sulcus and suggested that a larger ICL should be selected in eyes with a wide ciliary sulcus.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, a recent study conducted in healthy Chinese participants showed that the mean CPL was positively correlated with AL and negatively correlated with LT, which supported our findings of shorter AL and thicker LT in the insufficient vault group. 24…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, ophthalmology has significantly benefited from advances in vivo non-invasive ophthalmic imaging techniques that play currently a fundamental role in the clinical assessment, diagnosis, management, and monitoring of a wide variety of conditions involving both the anterior and posterior segment [1][2][3][4][5][6]. Imaging technologies, including anterior and posterior segment optical coherence tomography (OCT), OCT angiography, wide-field retinal imaging, specular and confocal microscopy, corneal topography, and ocular ultrasound, have dramatically improved the morphological and functional evaluation of ocular structures, both in healthy and pathological eyes [1][2][3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%